Genetic difference between African and Japanese scombropid populations based on cytochrome c oxidase subunit I gene sequences. Issue 1 (2nd January 2019) - Oyama, Hikaru; Itoi, Shiro; Ueda, Hiroyuki; Mochizuki, Yukako; Tanaka, Minori; Ito, Takeshi; Shishido, Hirotoshi; Masuda, Yasuji; Takai, Noriyuki; Sugita, Haruo
Abstract: The fish family Scombropidae consists of a single genus, Scombrops, and is distributed in the waters of the northwestern Pacific Ocean, southwestern Indian Ocean and western Atlantic Ocean, including the Caribbean Sea. Among these, the population of South Africa has been renamed from Scombrops dubius to Scombrops boops, which is known to be distributed in waters around Japanese Archipelago. We are skeptical of this revision as the two populations are geographically isolated between the waters of the Far East and the southern end of the Africa coast. Recently, our lab determined the sequences of the complete mitochondrial genome of three Japanese gnomefish, S. boops, Scombrops gilberti and an undescribed scombropid species ( Scombrops sp.). Here, we compared the partial sequence of cytochrome c oxidase subunit I (COI) from the three Japanese gnomefish with that of the African population. The African sequences showed 95.5â€"96.6% identity with the Japanese sequences, while the corresponding sequences from the Japanese species showed 98.2â€"100% identity with each other. A maximum likelihood tree based on the partial sequence of COI also demonstrated that the clade of African gnomefish is distinct from those of Japanese species including S. boops . These results suggest that the scombropid fish in the African waters is a different species from S. boops and that it is appropriate to resurrect the name Scombrops dubius for the African population.